2017
DOI: 10.4236/fns.2017.812085
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Risk Linked to the Consumption of Braised Beef Meat “<i>Choukouya</i>” Contaminated with Pathogenic <i>Clostridium perfringens</i> in Côte D’Ivoire

Abstract: Inadequate handling, processing and sales of meat products have resulted in microbial contamination responsible for most infectious human food-borne illness. The study conducted a stochastic assessment of the risk of infection linked to the consumption of braised beef meat "Choukouya" contaminated by Clostridium perfringens in Côte d'Ivoire. We conducted "Choukouya" consumers (n = 900) and vendors (n = 300) survey to characterize the actors behavior. 189 samples of "Choukouya" were collected and microbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Analysis of the different foods showed that the majority were not contaminated with Salmonella, this result is consistent with those of many studies conducted on street foods (El Marnissi et al, 2012;Diane et al, 2017;Boko et al, 2017;Dossou et al, 2018;Mayoré et al, 2018;Doutoum et al, 2019). In rice with sorrel sauce, there is a strong presence of Salmonella as in several other studies (Bereda et al, 2016;Justin et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Analysis of the different foods showed that the majority were not contaminated with Salmonella, this result is consistent with those of many studies conducted on street foods (El Marnissi et al, 2012;Diane et al, 2017;Boko et al, 2017;Dossou et al, 2018;Mayoré et al, 2018;Doutoum et al, 2019). In rice with sorrel sauce, there is a strong presence of Salmonella as in several other studies (Bereda et al, 2016;Justin et al, 2018).…”
Section: Discussionsupporting
confidence: 87%